Application of SGLT-2 inhibitors in non-diabetic CKD: mechanisms, efficacy, and safety - Zhang, Bing; Deng, Liufei (Frontiers in Medicine, 2025)
Chronic kidney disease (CKD) represents a major global public health challenge, significantly impacting patients’ quality of life and placing a heavy burden on healthcare systems. While diabetes and hypertension are the primary risk factors for CKD, non-diabetic CKD also constitutes a significant proportion, with its complex pathological mechanisms necessitating the development of novel therapeutic strategies. Sodium-glucose cotransporter 2 (SGLT-2) inhibitors, initially developed for diabetes management, have recently demonstrated remarkable renal and cardiovascular protective effects in patients with non-diabetic CKD. SGLT-2 inhibitors exert their effects through multiple mechanisms, including reactivating the tubulo-glomerular feedback, reducing glomerular pressure and filtration rate, decreasing proteinuria, inhibiting inflammation and fibrosis, and improving systemic metabolic parameters such as lowering blood pressure, uric acid levels, and body weight. These effects not only slow the progression of kidney function decline but also significantly reduce the risk of end-stage renal disease (ESRD) and cardiovascular events. Landmark clinical trials such as DAPA-CKD, CREDENCE, and EMPA-KIDNEY provide strong scientific evidence supporting the use of SGLT-2 inhibitors in non-diabetic CKD, demonstrating their broad clinical benefits and excellent safety profile. Despite potential adverse effects such as urinary tract infections, hypotension, and diabetic ketoacidosis, appropriate patient selection and personalized treatment strategies can effectively manage these risks. The multi-system effects of SGLT-2 inhibitors not only expand their clinical indications but also offer new hope for the comprehensive management of non-diabetic CKD patients, with significant clinical implications and broad future application potential.